IMPROVING THE METHODS OF PROBLEMS SOLVING RELATED TO SOLUTIONS IN 11TH GRADES (E Conference Zone, 2022)
In this article, improving the methods of problems solving related to solutions in 11 grades has been discussed. And also, different methods of problem solving in chemistry have been learned and analyzed.